A 72‐year‐old with eyelid opening apraxia in Steele–Richardson–Olszewski syndrome. Issue 6 (26th April 2017) - Qureshi, Ihtesham A.; Qureshi, Mohtashim A.; Maud, Alberto
Key Clinical Message: In our patient with Steele–Richardson–Olszewski syndrome presenting with apraxia of eyelid opening, there is a possibility to be readily confused with conditions presenting in similar pattern such as blepharospasm and eyelid ptosis. Therefore, it is essential to correlate the clinical findings with electromyographic recordings and dopamine transporter scan (DaT). Abstract : In our patient with Steele–Richardson–Olszewski syndrome presenting with apraxia of eyelid opening, there is a possibility to be readily confused with conditions presenting in similar pattern such as blepharospasm and eyelid ptosis. Therefore, it is essential to correlate the clinical findings with electromyographic recordings and dopamine transporter scan (DaT).